Management of Displaced Supracondylar Humerus Fracture in Children with Closed Reduction and Percutaneous Pinning - Ashraf , Mohammad Asim; Bakhsh , Karim; Ghani , Farhad; Ulusyar; Khan , Wali; Alamgeer , Muhammad; Jallat , Shamshair; Mehmood , Saddam (Indus Journal of Bioscience Research, 2025)
Background: One of the most frequent elbow injuries in kids that need surgery is a supracondylar humerus (SCH) fracture. For displaced SCH fractures, closed reduction and percutaneous pinning (CRPP) is generally regarded as the best course of treatment. Nonetheless, there is still much to learn about how well CRPP maintains fracture stability, avoids complications, and guarantees functional recovery. Objective: By analyzing functional and radiographic results, complication rates, and the influence of variables such fracture severity, surgical scheduling, and pinning procedures, this study seeks to determine how well CRPP manages displaced SCH fractures in children. Methods: In a Quetta tertiary care hospital, 150 children’s patients with displaced SCH fractures (Gartland Type II and III) between the ages of 3 and 12 were included in a qualitative study. Analysis was done on postoperative problems, surgical methods, patient demographics, and functional recovery. The study looked at the impact of surgical time on results and contrasted crossing and lateral-entry pinning. Reviews of medical records, interviews with surgeons, and clinical evaluations were used to gather data, and Flynn’s criteria were used to categorize the findings. Results: Of the 150 patients, 65.3% were male and 56.7% were between the ages of 3 and 6. The prevalence of Gartland Type III fractures was higher (63.3%). Because lateral-entry pinning has a lower risk of ulnar nerve injury, it was the technique of choice for 73.3% of respondents. In 90% of cases, surgery was done within 24 hours. 28% of patients experienced postoperative problems, with the most frequent ones being malunion (8%), ulnar nerve palsy (4.7%), and pin infections (5.3%). Functional results were good; according to Flynn’s criterion, 86.7% of patients had excellent or good performance. With 88% of parents reporting pleasant experiences, parent satisfaction was high. Conclusion: Children’s displaced SCH fractures can be safely and effectively treated using CRPP, which has a high success rate and little side effects. Reliable fixation with a lower risk of nerve damage is provided by lateral-entry pinning. Better results are obtained with early surgical intervention within 24 hours. According to these results, CRPP is the most effective treatment for pediatric patients with displaced SCH fractures.